Posibilidades y límites del crecimiento y desarrollo económico-social en países de Europa, Asia, África y américa Latina (2017)
From the perspective of the curse of resource theories and neo-extractivism and its theoretical background, the objective of the article is to highlight these referents with the realities of some countries interviewed in studies directed by researchers interested in the topic in question. As a result, experiences with favorable and unfavorable effects are identified regarding stimulation or delay to growth and development in countries of Europe, Asia, Africa, and Latin America, which economic model has based on extractive activities and production of raw materials, oriented to foreign trade.